Hubungan Lama Pemakaian Smartphone Dengan Tingkat Kualitas Tidur Pada Remaja Di Kabupaten Brebes - Rakhman, Arif; Prastiani, Dwi Budi; Permatasari, Eka Diana; Amalianti, Via (Universitas Tribhuwana Tunggadewi, 2023)
Adolescents had a problem in lack of fulfillment of sleep needs. This problem has increased along with changes in patterns and lifestyles. One of the lifestyles that are currently popular among adolescents is smartphone addiction. Prolonged use of smartphones before night bedtime will affect adolescent sleep patterns. The research aim is to determine the relationship between smartphone use and sleep quality in adolescents at MAN 1 Brebes. The research is a quantitative study with a cross-sectional approach to correlational research design. The research instrument used the “Kuesioner Penggunaan Smartphone” and Pittsburgh Sleep Quality Index Questionnaire. The study sample is 297 students recruited using stratified random sampling techniques. The inclusion criteria in the research were active students, willing to be respondents, and using smartphones. The data was analyzed using the Kendall-Tau correlation. The study result showed the majority of adolescents had a high frequency of smartphone use, and the quality of sleep was in the poor category. There was a relationship between smartphone use and the sleep quality of adolescents in Brebes with a value of Sig. (2-tailed) -0.08 (sig. 2-tailed) 0.005) and Correlation Coefficient 0.184 (very weak). Adolescents show poor sleep quality conditions with a high category in smartphone use.